Naringenin nanocrystals for improving anti-rheumatoid arthritis activity - Guangshuai Zhang; Guangyuan Sun; Haishan Guan; Mo Li; Yanhua Liu; Baocheng Tian; Zhonggui He; Qiang Fu (Elsevier, 2021)
Naringenin (NAR) is recognized for its anti-inflammatory activity. However, the clinical application of NAR is limited by low bioavailability, which is attributed to its poor aqueous solubility. In this study, we aimed to improve the therapeutic efficacy of NAR by formulating it into nanocrystals (NCs) via wet milling. The obtained NARNCs exhibited superior dissolution behaviors, increased cellular uptake, and enhanced transcellular diffusion relative to those of bulk NAR. Oral administration of NARNCs also significantly improved bioavailability in rats. In addition, the NARNCs effectively improved rheumatoid arthritis treatment in collagen-induced arthritic rats by reducing inflammatory cell infiltration and synovial damage. These results indicate that NARNCs provides a promising strategy for rheumatoid arthritis treatment.